Algorithms and Architectures for Parallel Processing 9th International Conference, ICA3PP 2009, Taipei, Taiwan, June 8-11, 2009. Proceedings - Hua, Arrems; Chang, Shih-Liang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the 9th International Conference on Algorithms and Architectures for Parallel Processing, ICA3PP 2009, held in Taipei, Taiwan, in June 2009. The 80 revised full papers were carefully reviewed and selected from 243 submissions. The papers are organized in topical sections on bioinformatics in parallel computing; cluster, grid and fault-tolerant computing; cluster distributed parallel operating systems; dependability issues in computer networks and communications; dependability issues in distributed and parallel systems; distributed scheduling and load balancing, industrial applications; information security internet; multi-core programming software tools; multimedia in parallel computing; parallel distributed databases; parallel algorithms; parallel architectures; parallel IO systems and storage systems; performance of parallel ditributed computing systems; scientific applications; self-healing, self-protecting and fault-tolerant systems; tools and environments for parallel and distributed software development; and Web service.
Bioinformatics in Parallel Computing -- Cluster, Grid and Fault-Tolerant Computing -- Clusterdistributed Parallel Operating Systems Middleware -- Dependability Issues in Computer Networks and Communications -- Dependability Issues in Distributed and Parallel Systems -- Distributed Scheduling and Load Balancing -- Industrial Applications -- Information Security Internet -- Multi-core Programming Software Tools -- Multi-medium in Parallel Computing -- Parallel Distributed Databases -- Parallel Algorithms -- Parallel Architectures -- Parallel IO Systems and Storage Systems -- Performance of Parallel Distributed Computing Systems -- Scientific Applications -- Self-healing Self-protecting and Fault-Tolerant Systems -- Tools and Environments for Parallel and Distributed Software Development -- Web Service.
Keywords: Computer science; Computer organization; Software engineering; Computer programming; Computers; Algorithms; Computer engineering; Computer Science; Software Engineering/Programming and Operating Systems; Computer Engineering; Programming Techniques; Computer Systems Organization and Communication Networks; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Electronic books